Right ventricular dysfunction and tricuspid regurgitation in functional mitral regurgitation. (22nd September 2021) - Truong, Vien T.; Ngo, Tam N.M.; Mazur, Jan; Nguyen, Hoai T.M.; Pham, Thuy T.M.; Palmer, Cassady; Pham, Khanh N.P.; Phan, Hoang T.; Lee, Kwan S.; Bannehr, Marwin; Butter, Christian; Gyoten, Takayuki; et al.
Abstract: Aim: The objective of this study was to investigate the prognostic importance of right ventricular dysfunction (RVD) and tricuspid regurgitation (TR) in patients with moderate–severe functional mitral regurgitation (FMR) receiving MitraClip procedure. RVD and TR grade are associated with cardiovascular mortality in the general population and other cardiovascular diseases. However, there are limited data from observational studies on the prognostic significance of RVD and TR in FMR receiving MitraClip procedure. Methods and results: A systemic review and meta‐analysis were performed using MEDLINE, Scopus, and Embase to assess the prognostic value of RVD and TR grade for mortality in patients with functional mitral regurgitation (FMR) receiving MitraClip procedure. Hazard ratios were extracted from multivariate models reporting on the association of RVD and TR with mortality and described as pooled estimates with 95% confidence intervals. A total of eight non‐randomized studies met the inclusion criteria with seven studies having at least 12 months follow‐up with a mean follow‐up of 20.9 months. Among the aforementioned studies, a total of 1112 patients (71.5% being male) were eligible for being included in our meta‐analysis with an overall mortality rate of 28.4% ( n  = 316). Of the enrolled patients, RVD was present in 46.1% and moderate–severe TR in 29.2%. RVD was significantly associated with mortality compared to normal RV function (HR, 1.79, 95% CI, 1.39–2.31, P  < 0.001, I 2  = 0). Patients with moderate–severe TR showed increased risk of mortality compared with those in the none‐mild TR group (HR, 1.61. 95% CI, 1.11–2.33, P  = 0.01, I 2  = 14). Conclusions: This meta‐analysis demonstrates the prognostic importance of RVD and TR grade in predicting all‐cause mortality in patients with significant FMR. RV function and TR parameters may therefore be useful in the risk stratification of patients with significant FMR undergoing MitraClip procedure.